Rewriting '9/11 or US invation of Iraq' Traumatic Memories in Shaila Abdullah's Saffron Dreams - Hasnul Insani Djohar (Faculty of Adab and Humanities, Syarif Hidayatullah State Islamic University of Jakarta., 2023)
This paper examines how the US-Pakistani Muslimahs or Muslim women live in the US after US Invasion of Iraq (2003) in Shaila Abdullah’s Saffron Dreams (2009). In the novel, Abdullah depicts her characters as victims of the 9/11 attacks to challenge US dominance in 9/11 narratives, which tend to show how the US becomes the victim, instead of the perpetrator of the US invasion of Iraq. By engaging with postcolonialism and 9/11 studies, this paper questions US anti-Muslim racism, which tends to associate Muslims with terrorism by exploring the ideas of trauma of being attacked by US extremists. This paper found that Abdullah’s Saffron Dreams depicts US Pakistani Muslimah struggling to seek social justice and US belonging. In doing so, this novel resists anti-Muslim racism by depicting its protagonists as facing several trauma, which is ironically continued by her next generation, who is suffering from multiple born defect representing their endless traumatic experiences living in the US after US invasion of Iraq. By exploring US-Pakistani-Muslimah stories, this novel suggests how the Pakistani Muslim diaspora not only struggles to live in the US after the US invasion of Iraq but also faces multiple trauma, especially being attacked by US extremists. This multiple trauma work to question US-trauma centric in dominant narratives. Thus, it is important to investigate traumatic stories from marginal experiences to undermine dominant narratives, which tend to exclude marginal memories after US invasion of Iraq from US belonging.